Long transmaxillary implants improve oral health-related quality of life of patients with atrophic jaws-a case series - Gino Kopp; João Cezar Zielak; Suyany Gabriely Weiss; Fernanda Kopp; Tatiana Miranda Deliberador (SpringerOpen, 2021)
Abstract Background The advancement of contemporary dentistry is related to the improvement of existing techniques, materials, and technology, consistently for improving people's oral health, which can ultimately reflect better quality of life. This study aimed to evaluate the oral-health-related quality of life (OHRQoL) of patients with atrophic jaws, who reported for the placement of long transmaxillary implants and posterior prosthetic rehabilitation. Twelve patients (n = 12), of both sexes, with a mean age of 55.83 ± 2.78 years, who were unable to receive conventional implants immediately because of lack of bone, received two long transmaxillary implants in a horizontal position, anteroposteriorly, one on each side, from the canine pillar to the maxillary tuberosity. After 6 months, the conventional clinical sequence for fabricating a fixed prosthesis type protocol or removable prosthesis type overdenture (MK1® system) was performed, when required to recover the lip volume. The Oral Health Impact Profile questionnaire (OHIP-14) was applied preoperatively and 6 months after rehabilitation using a prosthesis on the implants. The results were statistically analyzed using a significance level of 0.05. Results An improvement in the perception of OHRQoL was observed between the pre- and postoperative periods in the OHIP-14 total score and the domains related to functional limitation, physical pain, psychological discomfort, psychological disability, social disability, and handicap (p < 0.05). Conclusion It may be concluded that transmaxillary implant rehabilitation improves the OHRQoL.